PERSEPSI GURU. KEPALA SEKOLAH, DAN WALI MURID TENTANG FENOMENA KEKERASAN DI DUNIA MAYA TERHADAP ANAK - Hanifah Titi Ananingsih; Muhammad Ragil Kurniawan (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
In the current technological era many children are using social media. Children are more vulnerable to experiencing violence in cyberspace. The role of teachers, principals and guardians of students is needed to prevent the occurrence of violence in cyberspace. This study aims to determine the perceptions of teachers, principals, and guardians of students about the phenomenon of cyber violence against children. The subjects of this study were 4 teachers, 2 school principals, and 4 student guardians. Selection of subjects using purposive sampling technique. The object in this study is the perception of teachers, principals, and guardians of students about child violence in cyberspace. This research is a qualitative research with data collection techniques in the form of observation, interviews, and documentation. The validity of the data uses triangulation techniques with data analysis using an interactive model consisting of data collection, data reduction, display data, and conclusion drawing. The results of the study show that from (1) the cognitive aspects of teachers, principals and guardians of students who know about child violence in cyberspace prevent children from violence in cyberspace. (2) Affective aspects, feelings of teachers, principals and guardians of students are good, if children experience violence in cyberspace feel sad and sad. However, in the context of finding children who experience violence in cyberspace is still classified as passive. Teachers, principals and guardians of students will take action if there is a complaint from the child. (3) Conative aspects, when in school teachers and principals tend to act to prevent violence by advising children, prohibiting the use of mobile phones in schools and not providing internet support facilities for children. At home, guardians provide supervision and advice if children access the internet.